Spatiotemporal variation of Li isotopes in the Yarlung Tsangpo River basin (upper reaches of the Brahmaputra River): Source and process - Zhang, Jun-Wen; Yan, Ya-Ni; Zhao, Zhi-Qi; Liu, Xiao-Ming; Li, Xiao-Dong; Zhang, Dong; Ding, Hu; Meng, Jun-Lun; Liu, Cong-Qiang (Earth and planetary science letters, 2022)
The increase in marine Li isotope composition (δ7Li, ∼9‰) since the Cenozoic is possibly related to continental chemical weathering associated with tectonic uplift (e.g., the Tibetan Plateau [TP]). However, the reasons for the spatiotemporal variations of δ7Li in the rivers flowing through the TP are still under debate, hindering the understanding of the changes in seawater δ7Li. Herein, various geological samples, i.e. river waters, river suspended particulate materials, river sediments, hot springs and silicate rocks, from the Yarlung Tsangpo River basin, the largest river system in the TP, have been analyzed to understand the source and isotopic fractionation of dissolved Li in rivers flowing through high-altitude and tectonic regions. The Yarlung Tsangpo River has an unusually high dissolved Li concentration ([Li]dis) (0.5–313 μg/L, mean 58.4 μg/L, n=93) and low δ7Lidis values (+1.0‰–+14.7‰, mean +6.4‰, n=92) compared with most river waters. These results can be explained by the input of geothermal water with extremely high [Li]dis (5.5–34.4 mg/L, mean 15.7 mg/L, n=9) and low δ7Lidis (−1.7‰–+3.1‰, mean +1.0‰). Silicate weathering is probably responsible for elevated δ7Lidis in river water compared to geothermal water, but the binary mixture model results of silicate weathering and geothermal water do not support this speculation. Ongoing Li isotope fractionation between dissolved loads and secondary minerals has been suggested to be the main reason for the increased δ7Lidis in river water. Field study and adsorption experiment results support the view of continuous Li isotope fractionation in rivers. Physical erosion and chemical weathering processes that provide fresh secondary minerals to rivers as well as dissolved Li from geothermal water transported in rivers over long residence times promote Li isotope fractionation. Hence, with the emergence of a continental geothermal system, the tectonic activity may directly or indirectly induce the simultaneous increase in dissolved Li flux and δ7Lidis in rivers that eventually flow into the ocean. This can partially explain the increase in seawater δ7Li in the Late Cenozoic. •Li isotope composition is analyzed in the largest river system in Tibetan Plateau.•Dissolved load has very high [Li]dis, high Li/Na ratios, and low δ7Lidis values.•Geothermal water is responsible for the high [Li]dis and low δ7Lidis in river water.•Continental geothermal water increases in the Li flux and δ7Lidis in river estuaries.•The results help to explain the increase of seawater δ7Li in the late Cenozoic.